2019
DOI: 10.12820/rbafs.23e0053
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, sedentary time and bone tissue: effects of an 8-months interdisciplinary program with overweight/obese children

Abstract: Moderate to vigorous physical activity plays a recognized osteogenic effect on bone. Moreover, sedentary time, and fat accumulation are unfavorable to bone health. Our study aimed (1) to examine changes in body composition, bone tissue, physical activity, and sedentary time; and (2) to explore whether changes in physical activity intensities and in sedentary time are associated with changes in bone outcomes after a school-based interdisciplinary intervention program. A total of 53 overweight/obese students (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Therefore, the inclusion, on Physical Education (PE) classes, of exercises that assure efforts whose duration and intensity are conducive to the increase of bone mass, could be an important strategy for the health promotion 12 . Besides PE classes, the ingestion of calcium and D-vitamin, and hormonal factors [13][14][15][16] appear to be potential approaches to increase peak bone mass for this age group 17,18 . A recent scoping review 19 22 , who reported that the inclusion of simple exercises (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the inclusion, on Physical Education (PE) classes, of exercises that assure efforts whose duration and intensity are conducive to the increase of bone mass, could be an important strategy for the health promotion 12 . Besides PE classes, the ingestion of calcium and D-vitamin, and hormonal factors [13][14][15][16] appear to be potential approaches to increase peak bone mass for this age group 17,18 . A recent scoping review 19 22 , who reported that the inclusion of simple exercises (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the inclusion of Physical Education (PE) classes, of exercises that assure efforts whose duration and intensity are conducive to the increase of bone mass, could be an important strategy for the health promotion (García‐Hermoso et al, 2020). Besides PE classes, the ingestion of calcium and D‐vitamin, and hormonal factors (Agostinete et al, 2016; Bass et al, 2007; Karpiński, Popko, Maresz, Badmaev, & Stohs, 2017; Specker & Binkley, 2003) appear to be potential approaches to increase peak bone mass for this age group (Gómez‐Bruton, Matute‐Llorente, González‐Agüero, Casajús, & Vicente‐Rodríguez, 2017; Mello et al, 2018). A recent scoping review by Nguyen (2018) summarised the evidence of studies that implemented different osteogenic exercises in school PE classes, and although no meta‐analysis has been performed, the result indicated that PE classes are based on fun, organised and varied approaches, are opportune strategies for bone health promotion.…”
Section: Introductionmentioning
confidence: 99%